Contemporary Indian Perspectives on Cultural Morality and Euthanasia Acceptability - Ashim Mandal; Dr. K. Raveendran (Revista Electronica de Veterinaria, 2024)
Contemporary Indian perspectives on cultural morality and the acceptability of euthanasia are highlights the complex interplay between traditional values, religious worldviews, and emerging social developments. In India, the foundations of cultural morality are anchored in the sacredness of life, duties to family, and shared ethical responsibilities. Historically, these values have led to a cautious stance on euthanasia, frequently linking it with moral risk, social stigma, and concerns about misuse. Religious traditions—especially Hinduism, Buddhism, and Jainism—provide additional nuance by stressing ideas like karma, dharma, and the natural cycle of life and death, thereby bolstering conservative perspectives in numerous communities. India, however, is slowly undergoing a change in ethical thought. Factors such as urbanization, enhanced medical literacy, exposure to worldwide discussions, and the rising focus on personal autonomy have all played a role in fostering more candid conversations about dignified dying. The significance of patient choice, quality of life, and alleviation of long-term suffering is being underscored more and more by younger demographics, healthcare workers, and educated city-dwelling populations. The 2018 Supreme Court ruling that acknowledged passive euthanasia and living wills has added legitimacy to these developing viewpoints, fostering a transition from an exclusively traditional moral framework to one that incorporates compassion, autonomy, and constitutional rights. This article seeks to analyze the changing moral landscape by identifying the main cultural, religious, and social factors that shape public attitudes; evaluating the ethical tensions between duty-based morality and individual rights; and assessing how contemporary developments are transforming debates on the acceptability of euthanasia in India. The article provides a thorough understanding of the evolution of cultural morality and its influence on India’s current discussions regarding ethical end-of-life decision-making by combining theoretical insights with contemporary societal trends.